2011
DOI: 10.1111/j.1467-971x.2010.01656.x
|View full text |Cite
|
Sign up to set email alerts
|

English as an international language of scientific publication: a study of attitudes

Abstract: This paper focuses on an issue attracting increasing attention: the possible disadvantage inflicted on non-Anglophone academics by the dominance of English in scientific publication and academic exchange. We critically review the evidence for linguistic disadvantage, noting some of its limitations, and critique the native/non-native distinction as a coarse and somewhat unsatisfactory criterion for distinguishing between the advantaged and disadvantaged. In the second part of the paper we report on an empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(149 citation statements)
references
References 46 publications
4
118
0
3
Order By: Relevance
“…Results show that the number of scholarly research published in journals has steadily increased; that scientists consider English, used as a Lingua Franca, a convenient means to reach a wider audience and that findings are increasingly discussed by means of a more journalistic style connected to the race for priority and to the struggle for funding and for career advancement (Fanelli, 2012;Swales, 2004). Since English in academia will continue to be the dominant language of scientific communication (Ferguson, 2011), language practitioners' main goal should be to educate future experts cope with what non-native English speakers consider the English language burden (Benfield & Feak, 2006). This educational objective, already met by initiatives pivoted on the development of academic literacy and on research in the ESP/EAP field, has identified communicative practices based on the academic genres commonly employed by experts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results show that the number of scholarly research published in journals has steadily increased; that scientists consider English, used as a Lingua Franca, a convenient means to reach a wider audience and that findings are increasingly discussed by means of a more journalistic style connected to the race for priority and to the struggle for funding and for career advancement (Fanelli, 2012;Swales, 2004). Since English in academia will continue to be the dominant language of scientific communication (Ferguson, 2011), language practitioners' main goal should be to educate future experts cope with what non-native English speakers consider the English language burden (Benfield & Feak, 2006). This educational objective, already met by initiatives pivoted on the development of academic literacy and on research in the ESP/EAP field, has identified communicative practices based on the academic genres commonly employed by experts.…”
Section: Resultsmentioning
confidence: 99%
“…Results not published in English can be undervalued (Salager-Meyer, 2008) because any work written in languages other than English is not easily accessed by scholars who do not speak the language in which the research was published. The idea of translating relevant papers or of offering language editing services free of charge (Benfield & Feak, 2006), or paid by the universities researchers work with (Ferguson et al, 2011) is not feasible because of the economic costs that far outrun the benefits. In reply to those who fear for language loss, it should be stressed that in spite of everything, national idioms will be used to discuss topics dealing with regional key-points of interest published in local journals.…”
Section: Domain Loss: Benefit and Backwashmentioning
confidence: 99%
See 1 more Smart Citation
“…Faced with the veritable need to publish in English, certain studies have found that non-native English speaker (NNES) researchers are at a disadvantage on this English-only playing field [1,2], although other reports gather author perceptions that partially challenge this claim [4][5][6][7]. Real or perceived, the advantage enjoyed by researchers who are native English speakers (NESs) is not always considered by NNES authors to be an unfair one [8]. While some researchers state that English usage and style are not the reasons given by journals for rejecting submissions [9], others say just the opposite (Weller, 2001, cited in [10,11]).…”
Section: Introductionmentioning
confidence: 99%
“…Guidelines currently recommend reducing oral calcium intake, including calcium-based phosphate binders in hemodialysis patients, especially in the presence of adynamic bone disease, vascular calcification or hypercalcemia (6), to decrease the risk of vascular calcification (7). In this regard, over 60% of dialysis patients have adynamic bone disease (8). Dialysis calcium concentration ([calcium]) also contributes to calcium balance in hemodialysis patients (9,10).…”
Section: Genre Considerationsmentioning
confidence: 99%